Cost-Effectiveness of Office Hysteroscopy for Abnormal Uterine Bleeding - Moawad, Nash S. (Society of Laparoendoscopic Surgeons, 2014)
BACKGROUND AND OBJECTIVES: Office diagnostic hysteroscopy allows physicians to directly view the endometrial cavity, tubal ostia, and endocervical canal without taking the patient to the operating room (OR). We sought to determine whether office hysteroscopy performed to evaluate abnormal uterine bleeding decreases the need for hysteroscopy performed in the OR and the associated financial and risk implications. METHODS: One hundred thirty patients who underwent office diagnostic hysteroscopy between January 2009 and March 2012 at 2 outpatient clinics in an academic university setting were identified. Records were reviewed from paper charts and electronic medical records. Hospital charts for patients who required hysteroscopy in the OR were reviewed as well. Charge estimates were obtained from our billing department. These results were analyzed for review of the data. RESULTS: Seventy-five of the 130 women who underwent diagnostic office hysteroscopy for abnormal bleeding did not need to undergo hysteroscopy in the OR. This represents estimated savings of $1498 per patient (95% confidence interval, $1051–$1923) in procedure charges. Among the 55 women who underwent OR hysteroscopy, there was 71% agreement between findings on hysteroscopy in the office and in the OR. CONCLUSION: Office hysteroscopy is a useful diagnostic tool that can help decrease the rate of diagnostic hysteroscopy in the OR under anesthesia when used in a select patient population.